Full‐Genome Sequencing of Four Bluetongue Virus Serotype 11 Viruses. Issue 5 (8th October 2013) - Vandenbussche, F.; Sailleau, C.; Rosseel, T.; Desprat, A.; Viarouge, C.; Richardson, J.; Eschbaumer, M.; Hoffmann, B.; De Clercq, K.; Bréard, E.; Zientara, S.
Summary Recently, a contamination incident was described in which the challenge inoculum used in a bluetongue virus serotype 8 (BTV‐8) vaccination trial was contaminated with a BTV‐11 virus that was closely related to the Belgian BTV‐11 virus from 2008. This study reports the first complete genome sequences of four BTV‐11 viruses: the BTV‐11 contaminant, BTV‐11 reference strain, BTV‐11 vaccine strain and a recently isolated BTV‐11 field strain from Martinique. Full‐genome analysis showed that these viruses belong to serotype 11/nucleotype A and cluster together with other western topotype bluetongue viruses. Detailed comparisons of the genomes further indicated that the contaminant was derived from the BTV‐11 reference strain, as they were distinguished by a single synonymous nucleotide substitution. The previously reported partial sequence of genome segment 2 of the Belgian BTV‐11 was found to be identical to that of the BTV‐11 vaccine strain, indicating that it most likely was the BTV‐11 vaccine strain. These findings also suggest that the BTV‐11 contaminant and the Belgian BTV‐11 are not the same viruses. Finally, comparison of the reference and vaccine strain did not allow determining the amino acid substitutions that contribute to the attenuated phenotype.